Listeria monocytogenes Meningitis in Adults: The Czech Republic Experience. (11th September 2013) - Dzupova, Olga; Rozsypal, Hanus; Smiskova, Dita; Benes, Jiri
Abstract : Background . Listeria monocytogenes (LM) is currently the third most frequent pathogen of bacterial meningitis in adults. Methods . A prospective study of patients with LM meningitis in a Czech tertiary care hospital, carried out from 1997 to 2012. Results . Thirty-one patients were diagnosed with LM meningitis, which was 7% of a total of 440 adult patients with acute bacterial meningitis (ABM) over a 16-year period. Their median age was 63 years, range 26–80 years. Nineteen patients (61%) had underlying immunocompromising comorbidity; 15 patients (48%) were older than 65 years. Fourteen patients (45%) had arterial hypertension. The typical triad of fever, neck stiffness, and altered mental status was present in 21 patients (68%). The median count of cerebrospinal fluid (CSF) leukocytes was 680/μ L, protein level 2.6 g/L, and glucose ratio 0.28. Four patients (13%) died, and nine (29%) survived with moderate to severe sequelae. Conclusion . LM meningitis is known to affect immunosuppressed and elderly patients. Arterial hypertension seems to be another important predisposing factor. Clinical symptoms, CSF findings, and disease outcomes, did not significantly differ from other community-acquired ABM in our study, although the CSF leukocyte count was lower. Ampicillin showed good clinical and bacteriological efficacy in the majority of patients.